2018
DOI: 10.1080/00380253.2018.1481726
|View full text |Cite
|
Sign up to set email alerts
|

Are Biological Science Knowledge, Interests, and Science Identity Framed by Religious and Political Perspectives in the United States?

Abstract: Science trust and views of science differ by political and religious orientations. In this study we examine whether political and religious perspectives are also associated with biological science knowledge, science interest, and general science identity. Results show that conservative Protestants have lower biological science knowledge than other religious groups on several specific topics. Party affiliation is associated with vaccine knowledge but not science interest and identity. Adjusting for demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…Prior research has found that political conservatives and Republicans are more likely to hold anti-vaccine attitudes [3] , [4] , [6] , [17] , [22] , [24] , [25] , [32] , [33] , [42] . Recent research has also found that they are less likely to state that they plan to receive a COVID-19 vaccine [11] ; Gadarian, Goodman, and Pepinsky 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found that political conservatives and Republicans are more likely to hold anti-vaccine attitudes [3] , [4] , [6] , [17] , [22] , [24] , [25] , [32] , [33] , [42] . Recent research has also found that they are less likely to state that they plan to receive a COVID-19 vaccine [11] ; Gadarian, Goodman, and Pepinsky 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research shows that similar processes are potentially at work. Political conservatives have over time become more skeptical of science and scientific expertise, especially regarding vaccines (Buckman et al 2020; Hornsey et al 2018; Jochman et al 2018). We also find that Catholics and Americans who do not affiliate with a religious tradition are significantly more likely than Protestants to hold anti-vaccine beliefs even after accounting for Christian nationalism, religiosity, and politics.…”
Section: Discussionmentioning
confidence: 99%
“…We include several control measures known to be associated with anti-vaccine attitudes (Buckman et al 2020; Callaghan et al 2019; Hornsey et al 2018; Jochman et al 2018; McCoy 2020; Quinn and Lewin 2020). Our political control measures include political conservatism (1 = “extremely liberal” to 7 = “extremely conservative”) and political party (Republican [reference category], independent, or Democrat).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Moral and ethics itself cannot be separated from the guidance of religion. Ethics is one of importance factors of the relationship between religion and science [18], while both are believed to affect the state of education in some countries [19]. Religion is the core of the historical knowledge of science that contrasts sharply with social life [20].…”
Section: Ethnoscience and Its Relationship With Religious Sciencesmentioning
confidence: 99%